1970
DOI: 10.3329/ptcb.v20i2.6894
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium-mediated Genetic Transformation for Local Cultivars of Potato (Solanum tuberosum L.) Using Marker Genes

Abstract: Genetic transformation using nodal and internodal segments from three economically important potato (Solanum tuberosum L.) varieties namely, Diamant, Cardinal and Granola was conducted using an Agrobacterium tumefaciens strain LBA4404 harbouring binary plasmid pBI12 containing the GUS and nptII genes. Node and internodal segments were used for direct regeneration as well as regeneration with the intervention of callus. Best responses were obtained for direct regeneration of shoots when the explants were cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 7 publications
2
18
1
Order By: Relevance
“…reported for nodal and internal explants (Borna et al 2010, Hussain et al 2005, Sarker and Mustafa 2002, Philip and Hampson 1995, while for leaf and internodes, NAA and BAP were reported to be the best (Khatun et al 2012). Both studies are different from our observation.…”
Section: Resultscontrasting
confidence: 56%
See 1 more Smart Citation
“…reported for nodal and internal explants (Borna et al 2010, Hussain et al 2005, Sarker and Mustafa 2002, Philip and Hampson 1995, while for leaf and internodes, NAA and BAP were reported to be the best (Khatun et al 2012). Both studies are different from our observation.…”
Section: Resultscontrasting
confidence: 56%
“…This variation may be due to the different genotypes. Borna et al (2010) reported direct regeneration from node and internode explants. Hussain et al (2005) reported direct regeneration from node and shoot apex, while indirect regeneration occurred from leaf and internode.…”
Section: Resultsmentioning
confidence: 99%
“…Establishment of an efficient in vitro regeneration protocol is a prerequisite to facilitate successful plant genetic transformation (Soto et al 2007). In this context numerous in vitro regeneration protocols have been developed for potato (Borna et al 2010, Chakravarty and Wang-Pruski 2010, Shin et al 2011, Lopéz and Chaparro 2007. Reports are also available regarding the influence of genotype, type of explants and culture conditions on the efficiency of in vitro regeneration in potato cultivars (Sarker and Mustafa 2002).…”
Section: Introductionmentioning
confidence: 99%
“…our results have no similarity with the results obtained by Hussaini et al [31] because they used combination of different growth hormones viz, BAP, GA 3 , NAA and TDZ. They found best regeneration on media supplemented with combinations of BAP, GA 3 and TDZ.…”
Section: Discussionmentioning
confidence: 99%
“…Potato is a staple food crop of forty countries around the world [2]. Potato is a tuberous crop plant which belongs to Solanacea family [3]. Potato is a source of complex carbohydrates and antioxidants that provide energy and immunity to our body.…”
Section: Introductionmentioning
confidence: 99%